2014
DOI: 10.1111/inm.12074
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients with borderline personality disorder with the brief admission intervention: A phenomenological study

Abstract: Brief admission is a crisis intervention for patients with borderline personality disorder (BPD), and refers to a clinical admission at a psychiatric hospital for a period of 1-5 nights. Patients formulate a treatment plan together with their community mental health nurse about the maximum frequency allowed for these brief admissions. The purpose of the study was to describe the lived experiences of patients with BPD with use of the brief admission intervention. The study used a phenomenological approach. Incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 34 publications
1
70
0
3
Order By: Relevance
“…somewhat surprisingly, considering the widespread use of brief hospitalization schemes in the netherlands reported elsewhere (29), no dutch controlled studies concerning patient-controlled admission in the strict sense used in this review was identified. two dutch studies conducted by the same research group were identified during article selection; however, one lacked a control group (30) and the other was a review of articles already scrutinized and excluded (13). After being in contact with the dutch authors behind these studies, it appears that there are no further studies available on the dutch programs at this time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…somewhat surprisingly, considering the widespread use of brief hospitalization schemes in the netherlands reported elsewhere (29), no dutch controlled studies concerning patient-controlled admission in the strict sense used in this review was identified. two dutch studies conducted by the same research group were identified during article selection; however, one lacked a control group (30) and the other was a review of articles already scrutinized and excluded (13). After being in contact with the dutch authors behind these studies, it appears that there are no further studies available on the dutch programs at this time.…”
Section: Resultsmentioning
confidence: 99%
“…However, the rigorous manual selection process allowed for the conclusion that these criteria were not unduly narrow and that slightly more generous inclusion criteria would not have resulted in a broader array of relevant data. for example, the requirement that studies included for review should be designed as controlled studies only excluded two articles: one descriptive single case study (31) and one qualitative study regarding general experiences of useful and less useful elements of brief hospital admission in patients with borderline personality disorder (30). furthermore, allowing for a broader age span only yielded one further article: a study on adolescents hospitalized after a suicide attempt (32).…”
Section: Resultsmentioning
confidence: 99%
“…Over repeated experiences of BA, the structure and stabilizing aspects of BA generalizes to the individuals’ life outside of the hospital, leading to reduced reliance on acute and general psychiatric hospital admissions while remaining safe in times of crisis [13, 14]. By learning new ways of responding/not responding during crises, and staying safe regardless of current emotion, gains from psychotherapy engaged in concurrently with BA (treatment as usual: TAU) facilitates capability to manage subsequent crises without turning to self-harm and suicidal behaviour [15].…”
Section: Introductionmentioning
confidence: 99%
“…As a crisis management strategy, BA was rapidly adopted across most mental health service centers in the Netherlands. Helleman, Goossens, Kaasenbrood, and van Achterberg [13] conducted a phenomenological study involving 17 participants with lived experience of BA in the Netherlands. With respect to the key features of BA that were identified, participants endorsed: (i) the organization of the brief admission; (ii) the quality of the contact with a nurse over the course of BA; (iii) the restorative value of time out from daily life; and (iv) the experienced value of the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation